The anti-infective activity of punicalagin against Salmonella enterica subsp. enterica serovar typhimurium in mice1. Issue 7 (8th July 2015) - Li, Guanghui; Feng, Yuqing; Xu, Yunfeng; Wu, Qian; Han, Qi'an; Liang, Xiujun; Yang, Baowei; Wang, Xin; Xia, Xiaodong
<x xml:space="preserve">Abstract</x> Punicalagin, a major bioactive component of pomegranate peel, has an anti-infective effect against S. typhimurium infection in mice.